Pembatalan Sertfikat Hak Guna Bangunan Melalui Putusan Pengadilan Tata Usaha Negara - Chania Putri Ayu (JOURNAL SAINS STUDENT RESEARCH, 2024)
The National Land Agency, which was negligent in investigating the land history regarding the issuance of a land use right certificate, has caused harm to other parties, leading to the cancellation of the certificate through a court decision. The problem formulation consists of how the legal consequences of the cancellation of the building use right certificate by the court affect the affected party, and what the responsibility of the National Land Agency is as the authority in issuing the certificate. This research is normative legal research that examines various regulations related to the issues faced, as well as interviews to support the research results. The results of this thesis indicate that the legal consequences of the cancellation of the building use right certificate through a court decision for the affected party, in this case the Plaintiff, require the Plaintiff to submit a request for the issuance of a new certificate to the National Land Agency after the cancellation has been made. Meanwhile, the Defendant can no longer physically possess the land that previously belonged to the Plaintiff. The responsibility of the National Land Agency as the authority in issuing the certificate concerning the cancellation of the certificate through a court decision is limited to the cancellation of the land rights certificate as the disputed object. This cancellation is a manifestation of compliance with the court's decision that has permanent legal force